2015
DOI: 10.1103/physrevstper.11.020109
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of algebraic quantum notations

Abstract: [This paper is part of the Focused Collection on Upper Division Physics Courses.] The formalism of quantum mechanics includes a rich collection of representations for describing quantum systems, including functions, graphs, matrices, histograms of probabilities, and Dirac notation. The varied features of these representations affect how computations are performed. For example, identifying probabilities of measurement outcomes for a state described in Dirac notation may involve identifying expansion coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 26 publications
6
55
0
Order By: Relevance
“…Brookes and Etkina [101] analyzed the use of metaphors in QM (e.g., a "potential well") and hypothesized that a student could be "distracted by an overly literal interpretation." Gire and Price [102] showed evidence of student reasoning interacting with features of Dirac, wave function, and matrix notations. Modir and Sayer [61] examined students' group problem solving on a free particle problem and identify a mathematical resource called "pulling out" that aids them in sense making.…”
Section: B Research On Student Epistemologies In Qmmentioning
confidence: 99%
“…Brookes and Etkina [101] analyzed the use of metaphors in QM (e.g., a "potential well") and hypothesized that a student could be "distracted by an overly literal interpretation." Gire and Price [102] showed evidence of student reasoning interacting with features of Dirac, wave function, and matrix notations. Modir and Sayer [61] examined students' group problem solving on a free particle problem and identify a mathematical resource called "pulling out" that aids them in sense making.…”
Section: B Research On Student Epistemologies In Qmmentioning
confidence: 99%
“…We look at the representations chosen through the lens of structural aspects of quantum notations [4]. In our questions, the representations and the methods used to solve for the expectation value are linked.…”
Section: B Construction Of the Modelmentioning
confidence: 99%
“…For example, it is possible to solve for the expectation value using matrix equations, Dirac notation, or integral expressions. In different contexts, one method may be preferred, but research shows that students tend to be more comfortable using a single notation and use it in most contexts [4]. Our study is designed to probe how students solve for expectation values of angular momentum operators and which representation they choose to use.…”
Section: Introductionmentioning
confidence: 99%
“…Students who construct the diagram unprompted tend to do better at integrating the diagram with conceptual reasoning. Others, for example Gire et al [9] and Parnafes [10], have shown that different physical features within representations may serve different roles in student reasoning, providing support for computation or for conceptual ideas such as "fast." The picture that emerges from these studies is that representation use by physics learners is contextual and tied closely with their conceptual reasoning.…”
Section: Introductionmentioning
confidence: 99%